Is the ballan wrasse (Labrus bergylta) two species? Genetic analysis reveals within‐species divergence associated with plain and spotted morphotype frequencies - QUINTELA, María (Integr Zool, 2016)
The ballan wrasse (Labrus bergylta) is a marine fish belonging to the family Labridae characterized by 2 main morphotypes that occur in sympatry: spotty and plain. Previous studies have revealed differences in their life‐history traits, such as growth and maturation; however, the genetic relationship between forms is presently unknown. Using 20 recently developed microsatellite markers, we conducted a genetic analysis of 41 and 48 spotty and plain ballan wrasse collected in Galicia (northwest Spain). The 2 morphotypes displayed highly significant genetic differences to each other (F (ST) = 0.018, P < 0.0001). A similar degree of genetic differentiation (F (ST) = 0.025, P < 0.0001) was shown using the STRUCTURE clustering approach with no priors at K = 2. In this case, the frequency of spotty and plain morphotypes was significantly different (χ(2) = 9.46, P = 0.002). It is concluded that there is significant genetic heterogeneity within this species, which appears to be highly associated with the spotty and plain forms, but not completely explained by them. Given the previously demonstrated biological differences between morphotypes, and the present genetic analyses, we speculate about the convenience of a taxonomic re‐evaluation of this species.